2011
DOI: 10.1002/jpln.201000046
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of soluble organic nitrogen, nitrogen mineralization, nitrification, and amidohydrolase activities in a manure‐treated soil

Abstract: Recent studies indicate that soil soluble organic nitrogen (SON) plays an important regulatory role in the soil-plant N cycle. The aims of this study were to identify the vertical distribution of SON and its correlation with N mineralization, nitrification, and amidohydrolase activities, in a soil repeatedly amended with cow manure or chemical fertilizer. For this purpose, soil samples were collected from 0-20, 20-40, 40-60, 60-80, and 80-100 cm depths of a calcareous soil, which has been annually amended for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
2
12
0
2
Order By: Relevance
“…The current general consensus is that manure application leads to a substantial increase in soil N mineralization potential and enhances the activity of heterotrophic microorganisms in the added organic manure; subsequent turnover of this microbial population will lead to the production of NH 4 + -N (Bonkowski et al, 2000). Additionally, manure preserves a certain amount of mineral N and dissolved organic N (Khalili and Nourbakhsh, 2012), both of which are continuously released from the manure due to mineralization, thereby increasing the soil Table 3. Stepwise regression analysis between N fractions and fruit yield during the tomato growth period.…”
Section: Effects Of Fertilization On N Fractionsmentioning
confidence: 99%
“…The current general consensus is that manure application leads to a substantial increase in soil N mineralization potential and enhances the activity of heterotrophic microorganisms in the added organic manure; subsequent turnover of this microbial population will lead to the production of NH 4 + -N (Bonkowski et al, 2000). Additionally, manure preserves a certain amount of mineral N and dissolved organic N (Khalili and Nourbakhsh, 2012), both of which are continuously released from the manure due to mineralization, thereby increasing the soil Table 3. Stepwise regression analysis between N fractions and fruit yield during the tomato growth period.…”
Section: Effects Of Fertilization On N Fractionsmentioning
confidence: 99%
“…A soil with a history of chicken-manure application increased EON significantly in the 0-150 cm soil profile compared to the same soil without manure addition (Shepherd et al 2001). A study from Khalili and Nourbakhsh (2012) even showed that EON was a major N pool in the whole profile of the manure applied soil. Meanwhile, manure application also results in more leaching of N than chemical fertilizer application at the same rate of N input (Chen et al 2005;van Kessel et al 2009).…”
Section: Introductionmentioning
confidence: 87%
“…Soil nitrification rates have been extensively measured in manured soils (Laanbroek and Gerards 1991;Nugroho and Kuwatsuka 1992;Paul et al 1993;Shi et al 2004;Calderón et al 2005;Habteselassie et al 2006;Khalili and Nourbakhsh 2012). Most studies have generally reported greater nitrification rates for amended than unamended or inorganic fertilized soils.…”
Section: Introductionmentioning
confidence: 99%